2020
DOI: 10.1016/j.jaad.2019.08.019
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and safety of apremilast in pediatric patients with moderate to severe plaque psoriasis: Results from a phase 2 open-label study

Abstract: Background: No oral systemic treatments are approved for pediatric patients with psoriasis.Objective: To evaluate the pharmacokinetics and safety of apremilast, an oral phosphodiesterase 4 inhibitor, in pediatric patients with psoriasis.Methods: This phase 2, multicenter, open-label study enrolled pediatric patients with moderate to severe plaque psoriasis. Patients received apremilast twice daily without titration for 2 weeks (group 1 [age, 12-17 years; weight, $35 kg]: apremilast 20 or 30 mg; group 2 [age, 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 24 publications
0
22
0
Order By: Relevance
“…The only study that reported on the efficacy of apremilast was a clinical trial by Paller et al (42 patients aged 6 to 17). 87 The participants were divided into three study groups consisting of children and adolescents with moderate to severe plaque psoriasis. The groups were based on age and weight-based doses.…”
Section: Apremilastmentioning
confidence: 99%
“…The only study that reported on the efficacy of apremilast was a clinical trial by Paller et al (42 patients aged 6 to 17). 87 The participants were divided into three study groups consisting of children and adolescents with moderate to severe plaque psoriasis. The groups were based on age and weight-based doses.…”
Section: Apremilastmentioning
confidence: 99%
“…Apremilast has been approved by the FDA for use in adult psoriasis and psoriatic arthritis since 2014 and for use in treating oral ulcers of Behçet disease since 2019. [1][2][3]5,6 Recently, a phase 2, multicenter, open-label study on the use of apremilast in pediatric psoriasis patients (aged 12-17 years) demonstrated a similar safety profile with weight-based dosing 8 ; phase 3 trials in this population are in the recruitment phase (ClinicalTrials.gov Identifier NCT03701763).…”
Section: On-label Usage Profilementioning
confidence: 99%
“…Phase II pediatric trial reveals only significant adverse effects are mild GI issues and upper tract respiratory infections on weight-based dosage regimen. 94,95 Contraindicated for pregnant and breastfeeding women, though animal models do not reveal any correlation between Apremilast and harmful effects on fetal development  Safety and effectiveness in pediatric patients < 18 years of age have not been established.  Pregnancy Category C: used during pregnancy only if potential benefit justifies the risk to the fetus.…”
Section: Apremilastmentioning
confidence: 99%